Colchicine and diabetes in patients with chronic coronary artery disease: insights from the LoDoCo2 randomized controlled trial - Mohammadnia, Niekbachsh; Los, Jan; Opstal, Tjerk S. J.; Fiolet, Aernoud T. L.; Eikelboom, John W.; Mosterd, Arend; Nidorf, Stefan M.; Budgeon, Charley A.; Tijssen, Jan G. P.; Thompson, Peter L.; Tack, Cees J.; Simsek, Suat; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Despite optimal treatment, patients with chronic coronary artery disease (CAD) and diabetes mellitus (DM) are at high risk of cardiovascular events, emphasizing the need for new treatment options. The Low-Dose Colchicine 2 (LoDoCo2) trial demonstrated that colchicine reduces cardiovascular risk in patients with chronic CAD. This analysis determines the efficacy of colchicine in patients with chronic CAD and DM as well as the effect of colchicine on the development of new-onset type 2 diabetes mellitus (T2DM). Methods The LoDoCo2 trial randomized 5,522 patients to placebo or colchicine 0.5 mg once daily, with a median follow-up of 28.6 months. The primary composite endpoint was cardiovascular death, spontaneous myocardial infarction, ischemic stroke, or ischemia-driven revascularization. The effect of its treatment in patients with and without DM was evaluated by including an interaction term in the model. Results A total of 1,007 participants (18.2%) had T2DM at baseline. The adjusted hazard ratio (HR) [(95% confidence interval (CI)] for the primary endpoint in the T2DM group was 1.52 (1.15–2.01, p < 0.01) compared with the group without T2DM. The HR for the treatment effect on the primary endpoint was 0.87 (0.61–1.25) in participants with T2DM and 0.64 (0.51–0.80) in participants without diabetes (pinteraction = 0.14). The incidence of new-onset T2DM was 1.5% (34 out of 2,270) in the colchicine group and 2.2% (49 out of 2,245) in the placebo group (p = 0.10). Discussion In conclusion, based on the current evidence, the beneficial effects of colchicine on cardiovascular endpoints are consistent regardless of DM status. The potential benefits of colchicine in preventing new-onset DM need further investigation. These findings are only hypothesis-generating and require larger prospective trials to confirm the results.